The competent doctor: a paper for discussion - Black, Carol (Clin Med (Lond), 2004)
The clinical competence of doctors needs to be defined and assessed in relation to the circumstances of individual practice, in terms of knowledge and skills, both clinical and communicative, as well as attitudes and behaviour. The need to identify the role of the medical practitioner in the context of team working is important and this position requires the skills of diagnosis, synthesis of information and prioritisation of investigation and treatment. Completion of training and acquisition of the Certificate of Completion of Specialist Training (CCST) lead to inclusion in the Specialist Register thus defining the specialist; elevation of a specialist to consultant status in the NHS requires the potential to acquire with maturity, both of person and experience, the confidence to take responsibilities for handling difficult situations, to manage uncertainties in clinical encounters and to guide younger doctors in their careers.